Principal components analysis to evaluate complex association of polymorphisms in ACE and ACTN3 genes and the extent of cardiovascular adaptive changes in elite athletes - Petrovic, T.; Djelic, M.; Zdravkovic, M.; Gavrilovic, T.; Atanasijevic, N.; Stojkovic, O. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Present article aims at clarifying the association of ACE and ACTN3 polymorphisms with adaptive heart changes in elite athletes from power, endurance and mixed sport disciplines using the principal component analysis (PCA). METHODS: Overall, 281 elite male athletes are divided into three groups: strength-type sports, endurance and mixed sports. After anthropometric measurements, physical and ultrasound examination of the heart, the athletes were exposed to a physical load test. All groups were analyzed for functional ACE and ACTN3 polymorphisms. In order to convert a set of examined, possibly correlated adaptive cardiovascular changes into a set of values of linearly uncorrelated variables we used principal component analysis (PCA). RESULTS: The type of sport significantly affects not only the athlete`s anthropometric characteristics, but also on the scope and specificity of the investigated adaptive cardiovascular changes. Athletes from the mixed group of sports showed the best working efficiency of the heart. PCA showed that the type of sport, but not genetic predisposition affects the co-adaptation of complex traits. CONCLUSIONS: Effect of genotype, type of sport and their interaction on observed variability in morpho-functional cardiovascular adaptive changes in elite athletes can be used for a better understanding of the clinical phenomenon of athlete`s heart and sudden cardiac death syndrome.